Developing digital transformation capability - Dragičević, Nikolina (Dynamic relationships management journal, 2022)
This paper integrates the individual ambidexterity, digital transformation, and dynamic capabilities literatures to develop a framework that helps to understand the role of managerial ambidextrous learning in building the digital transformation capability of an organization. Based on a comprehensive literature review, the paper identifies competing demands in terms of managerial learning orientation serving as microfoundations of different dynamic organizational capabilities underpinning digital transformation. We adopt an ambidextrous perspective of learning and propose that managers need to balance explorative and exploitative learning to aid building digital transformation capabilities. This paper contributes to ambidexterity and dynamic capabilities theoretical perspectives through its distinctive focus on the role of individual-level learning in the context of organizational-level digital transformation. The paper enhances understanding of how firms may support digital efforts by becoming sensitive to and supporting managerial ambidexterity as a critical factor in a successful digital transformation journey. We suggest that future research efforts should investigate empirically the role of managerial ambidextrous behavior in digital efforts.
Keywords: digitalizacija; digitalization; enterprises; management; podjetja